LEPR hypomethylation is significantly associated with gastric cancer in males - Yu, Hang; Pan, Ranran; Qi, Yuanling; Zheng, Zhonghua; Li, Jing; Li, Hongxiang; Ying, Jieer; Xu, Mingqing; Duan, Shiwei (Experimental and molecular pathology, 2020)
Previous study has shown LEPR is a candidate gene of prediction and treatment of gastric cancer (GC). The purpose of this study was to test whether LEPR methylation could predict the risk of GC. Tumor tissues and 5-cm adjacent non-tumor tissues from 117 newly diagnosed and untreated GC patients were collected for the current methylation study. LEPR methylation levels were determined by quantitative methylation specific PCR (qMSP), and the methylation level of LEPR was described by the percentage of methylated reference (PMR). Our results showed that LEPR methylation levels were significantly lower in tumor tissues than those in adjacent non-tumor tissues (median PMR: 36.64% vs. 50.29%, P = 1E-4). In addition, LEPR methylation levels were found to be significantly associated with platelet (r = −0.198, P = .037). Further subgroup analysis showed that the association of LEPR promoter hypomethylation with GC was specific to males (males: P = 7E-5; females: P = .500). Notably, significant hypomethylation of LEPR promoter was found only in GC patients without recurrence (P = .002) but not in GC patients with recurrence (P = .146). The AUC of LEPR hypomethylation for identification of GC risk was 0.649 with a sensitivity of 67.5% and a specificity of 63.2%. In addition, the AUC of LEPR hypomethylation in males was 0.685 with a sensitivity of 68.4% and a specificity of 69.6%. LEPR hypomethylation can be used to predict the risk of GC in males. And it might also have the potential to predict the recurrence in GC patients. •For the first time, we found that hypomethylation of the LEPR promoter was associated with the risk of gastric cancer.•Male patients mainly contributed to the association between LEPR hypomethylation with gastric cancer.•Besides, the association of LEPR hypomethylation with gastric cancer was observed in the patients without recurrence.